Transforming Narrative Text Instruction in Senior High School: Integrating Digital Storytelling and the SFL-GBA Approach - Yustika Nur Fajriah; Sinta Dewi; Lucky Rahayu Nurjamin; Asep Nurjamin; Anggia Nastya (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
In the digital era, learning increasingly involves multimodal resources, yet explicit teaching of how images and texts contribute to meaning-making through digital storytelling remains underexplored. This study examines the integration of Systemic Functional Linguistics Genre-Based Pedagogy (SFL-GBA) into the teaching of multimodal narrative texts at a private senior high school. A case study was conducted with 28 tenth graders through a team-teaching approach involving an English teacher and a lecturer, with data collected from eight classroom observations. Findings reveal that SFL-GBA effectively supported multimodal learning: during the Building Knowledge of the Field (BKoF) and Modeling of the Text (MoT) stages, students analyzed Field, Tenor, and Mode across texts and images, while in the Joint and Independent Construction stages, they composed narrative texts and transformed them into digital storytelling projects. The study concludes that explicit scaffolding and culturally responsive teaching within SFL-GBA enhance students’ multimodal literacy and narrative competence through digital storytelling. These findings also have important pedagogical implications, indicating that SFL-GBA can guide teachers in designing multimodal instruction and inform future curriculum development for integrating digital storytelling.